Effect of nano silica and fine silica sand on compressive strength of sodium and potassium activators synthesised fly ash geopolymer at elevated temperatures - Shaikh, Faiz; Haque, S. (John Wiley and Sons Ltd., 2018)
Environment friendly geopolymer is a new binder which gained increased popularity due to its better mechanical properties, durability, chemical resistance, and fire resistance. This paper presents the effect of nano silica and fine silica sand on residual compressive strength of sodium and potassium based activators synthesised fly ash geopolymer at elevated temperatures. Six different series of both sodium and potassium activators synthesised geopolymer were cast using partial replacement of fly ash with 1%, 2%, and 4% nano silica and 5%, 10%, and 20% fine silica sand. The samples were heated at 200°C, 400°C, 600°C, and 800°C at a heating rate 5°C per minute, and the residual compressive strength, volumetric shrinkage, mass loss, and cracking behaviour of each series of samples are also measured in this paper. Results show that, among 3 different NS contents, the 2% nano silica by wt. exhibited the highest residual compressive strength at all temperatures in both sodium and potassium-based activators synthetised geopolymer. The measured mass loss and volumetric shrinkage are also lowest in both geopolymers containing 2% nano silica among all nano silica contents. Results also show that although the unexposed compressive strength of potassium-based geopolymer containing nano silica is lower than its sodium-based counterpart, the rate of increase of residual compressive strength exposed to elevated temperatures up to 400°C of potassium-based geopolymer containing nano silica is much higher. It is also observed that the measured residual compressive strengths of potassium based geopolymer containing nano silica exposed at all temperatures up to 800°C are higher than unexposed compressive strength, which was not the case in its sodium-based counterpart. However, in the case of geopolymer containing fine silica sand, an opposite phenomenon is observed, and 10% fine silica sand is found to be the optimum content with some deviations. Quantitative X-ray diffraction analysis also shows higher amorphous content in both geopolymers containing nano silica at elevated temperatures than those containing fine silica sand.